1997
DOI: 10.1029/97gl01207
|View full text |Cite
|
Sign up to set email alerts
|

High resolution OI (630 nm) image measurements of F‐region depletion drifts during the Guará Campaign

Abstract: Abstract.A high performance, all-sky, imaging system has pro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
57
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 9 publications
13
57
0
Order By: Relevance
“…The climatology and characteristics of low-latitude F-region plasma drift have been extensively studied over the past few decades using ground-based radar observations, optical measurements, ionosonde, and satellite observations [1,2,3,4,5,6,7,8]. The previous studies have shown that the night-time zonal plasma drifts in geomagnetically quiet days were eastward while plasma drift during the geomagnetic disturbance days are westward.…”
Section: Introductionmentioning
confidence: 99%
“…The climatology and characteristics of low-latitude F-region plasma drift have been extensively studied over the past few decades using ground-based radar observations, optical measurements, ionosonde, and satellite observations [1,2,3,4,5,6,7,8]. The previous studies have shown that the night-time zonal plasma drifts in geomagnetically quiet days were eastward while plasma drift during the geomagnetic disturbance days are westward.…”
Section: Introductionmentioning
confidence: 99%
“…Liu (jyliu@jupiter.ss.ncu.edu.tw) bubbles (EPBs) associated with Equatorial Spread-F (ESF) irregularities (Mendillo and Baumgardner, 1982;Sahai et al, 2000;Fagundes et al, 1999;Taylor et al, 1997;Sinha et al, 2001;Kelley et al, 2002;Makela et al, 2004;Mendillo et al, 2005;Rajesh et al, 2007). The irregularities are generated at the magnetic equator when suitable conditions exist at the F-region bottom-side in the post-sunset period, and manifest themselves as dark bands of intensity depletions in the airglow images taken from equatorial and low-latitude stations (Weber et al, 1978;Mendillo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Once produced in the post-sunset equatorial ionosphere, plasma bubbles appear as localized decreases in airglow brightness and can be tracked across the nightside to determine their zonal drift speed. Under the assumption that these depletions are embedded in the surrounding plasma, one can equate the bubble drift speed with the drift of the ambient ionospheric plasma (Mendillo and Baumgardner, 1982;Taylor et al, 1997;Pimenta et al, 2003).…”
Section: Introductionmentioning
confidence: 99%